Case report: A rare case of retroperitoneal kaposiform hemangioendothelioma with spinal involvement without abnormal platelet count in 18F-FDG PET/CT - Qiu, Yongkang; Chen, Zhao; Yang, Qi; Huang, Wenpeng; Song, Lele; Fan, Yan; Kang, Lei (Frontiers in Medicine, 2022)
Kaposiform hemangioendothelioma (KHE) is a rare vascular neoplasm that mostly appears in infancy or early childhood. Most KHE occurred on the limbs and trunk with cutaneous lesions. Approximately 12% of KHE patients manifested as deep masses and spinal involvement is extremely rare. KHE may develop into life-threatening thrombocytopenia and consumptive coagulopathy, known as the Kasabach-Merritt phenomenon (KMP), especially in patients with retroperitoneal involvement. The thrombocytopenia is usually severe, with a median platelet count of 21×109/L at the initial presentation of KMP. Here, we firstly described a case of a 13-month-old girl with KHE who presented the movement limitation of the lower extremity caused by spinal involvement with a normal platelet count. 18F-FDG PET/CT showed mildly elevated metabolism in the lesion, suggesting a probably low-grade malignant tumor. Then the patient was diagnosed with KHE by biopsy. After 6-month sirolimus monotherapy, the size of the retroperitoneal lesion was reduced significantly and the patient showed improvement in clinical symptoms. This case demonstrated the advantage of 18F-FDG PET/CT in the evaluation of disease activity in KHE and the possibility of using 18F-FDG PET/CT to guide therapy and prognostication.